2018
DOI: 10.7717/peerj.5186
|View full text |Cite
|
Sign up to set email alerts
|

Identification of exosome-like nanoparticle-derived microRNAs from 11 edible fruits and vegetables

Abstract: Edible plant-derived exosome-like nanoparticles (EPDELNs) are novel naturally occurring plant ultrastructures that are structurally similar to exosomes. Many EPDELNs have anti-inflammatory properties. MicroRNAs (miRNAs) play a critical role in mediating physiological and pathological processes in animals and plants. Although miRNAs can be selectively encapsulated in extracellular vesicles, little is known about their expression and function in EPDELNs. In this study, we isolated nanovesicles from 11 edible fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
236
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(243 citation statements)
references
References 63 publications
(98 reference statements)
4
236
1
2
Order By: Relevance
“…It is necessary to establish the possibilities for these miRNAs to enter the human and animal organisms. Several studies have shown that miRNAs in various parts of plants are present in exosomes 30-400 nm in size and are distributed in the body as part of these nanoparticles (Bang & Thum, 2012; Denzer et al, 2000; Xiao et al, 2018). Such compaction of miRNAs in exosomes contributes to their conservation and facilitates the entry of miRNAs into animals through the digestive tract (Redis et al, 2012; Théry, Zitvogel & Amigorena, 2002; Valadi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to establish the possibilities for these miRNAs to enter the human and animal organisms. Several studies have shown that miRNAs in various parts of plants are present in exosomes 30-400 nm in size and are distributed in the body as part of these nanoparticles (Bang & Thum, 2012; Denzer et al, 2000; Xiao et al, 2018). Such compaction of miRNAs in exosomes contributes to their conservation and facilitates the entry of miRNAs into animals through the digestive tract (Redis et al, 2012; Théry, Zitvogel & Amigorena, 2002; Valadi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also speculate that exosomes liberated from digested edible plants may be a way of cross-species communication. Recently, plant derived exosome-like nanovescicles, having a structure similar to those of mammalian exosomes, have been characterized in different edible plant [90]. These nanovescicles can be absorbed in the mammalian gastrointestinal tract and have the potential to mediate plant-animal intercellular communication [91,92].…”
Section: Mirnas and Evolutionmentioning
confidence: 99%
“…In reference to the current efforts to use EXs as drug delivery systems, it should be highlighted that despite the identified very high organotropism of EXs derived from cancer cells, a shift to safer alternatives such as EXs produced from foods, has been recently made in this research field. From all the relevant sources of this category, bovine milk-and fruit-derived EXs are probably the most investigated for the purpose [72]. Indeed, bovine milk has been proposed as a scalable source of exosomes that can act as a carrier for chemotherapeutic/chemopreventive agents [73].…”
Section: Sources Of Exosomesmentioning
confidence: 99%